Trends in Western North Pacific Tropical Cyclone Intensity Change Before Landfall - Liu, Qingyuan; Song, Jinjie; Klotzbach, Philip J. (Frontiers in Earth Science, 2021)
This study investigates the long-term trend in the average 24-h intensity change (ΔV24) of western North Pacific (WNP) tropical cyclones (TCs) before landfall during June-November for the period from 1970-2019. We find a significant increasing trend in basin-averaged ΔV24 during 1970-2019. The increase in ΔV24 is significant over the northern South China Sea (17.5°-25°N, 107.5°-120°E) and to the east of the Philippines (7.5°-15°N, 122.5°-132.5°E), implying a slower weakening rate before landfall for the South China Sea and an increased intensification rate before landfall for the region east of the Philippines. We find a significant linkage between changes in ΔV24 and several large-scale environmental conditions. The increased ΔV24 before landfall in the above two regions is induced by a warmer ocean (e.g. higher sea surface temperatures, maximum potential intensity and TC heat potential) and greater upper-level divergence, with a moister mid-level atmosphere also aiding the ΔV24 increase east of the Philippines. Our study highlights an increasing tendency of ΔV24 before landfall, consistent with trends in ΔV24 over water and over land as found in previous publications.